2015
DOI: 10.1017/s002966511500169x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle loss and obesity: the health implications of sarcopenia and sarcopenic obesity

Abstract: Conference on 'Nutrition and age-related muscle loss, sarcopenia and cachexia' Symposium 4: Sarcopenia and cachexia and social, clinical and public health dimensionsMuscle loss and obesity: the health implications of sarcopenia and sarcopenic obesity S. Goya Wannamethee* and Janice L. AtkinsDepartment of Primary Care and Population Health, University College London, Royal Free Campus, London NW3 2PF, UK This paper reviews the health implications of obesity, sarcopenia and sarcopenic obesity on CVD and mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
219
1
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 310 publications
(243 citation statements)
references
References 71 publications
9
219
1
14
Order By: Relevance
“…It has been demonstrated previously that patients can have low skeletal muscle and be obese, which may explain why these measures outperformed BMI in our data set. 17 It is also well described that while albumin and prealbumin correlate with nutritional state in healthy individuals, their nature as acute-phase reactants limits interpretation in the clinical setting. Our findings complement previous work by Heberton et al, 7 which demonstrated the prognostic ability of psoas muscle area determined by CT.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated previously that patients can have low skeletal muscle and be obese, which may explain why these measures outperformed BMI in our data set. 17 It is also well described that while albumin and prealbumin correlate with nutritional state in healthy individuals, their nature as acute-phase reactants limits interpretation in the clinical setting. Our findings complement previous work by Heberton et al, 7 which demonstrated the prognostic ability of psoas muscle area determined by CT.…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence that lifestyle interventions, such as exercise training and to a lesser extent nutritional supplementation, may improve or maintain muscle, fat and performance outcomes in men treated with ADT, which may in turn reduce the likelihood of further clinical complications [14,[56][57][58][59] . To date, previously evaluated interventions have been limited to singular modalities (e.g.…”
Section: List Of Tables Chaptermentioning
confidence: 99%
“…Despite these findings, the use of ADT is commonly prescribed to men with both metastatic [3] and non-metastatic PCa [4] . In 2008-09, it was estimated that 23,500 Australian men received ADT via GnRH agonists [56] . Upon repeating this analysis for 2014-15, approximately 25,500 men were receiving ADT via GnRH agonists [71] .…”
Section: Androgen Deprivation Therapymentioning
confidence: 99%
See 2 more Smart Citations